A simplified reinforcement and fracture mechanism analysis model of epoxy nanocomposites based on finite element simulation. (26th May 2022) - Lin, Lijie; Wang, Yingzhu; Lin, Zhiyong; Luo, Weiang; Zhang, Hong; Chen, Guorong; Cao, Hesheng; Yuan, Conghui; Xu, Yiting; Zeng, Birong; Dai, Lizong
Abstract: Understanding the reinforcement and fracture mechanism of polymer matrix nanocomposites is crucial for the design of high-performance composite materials. By taking boron nitride@boronate polymer core-shell nanoparticles modified epoxy resin nanocomposites (EPNCs) as an example, a reinforcement and fracture mechanism analysis model of nanocomposites was established through the combination of experiments and simulations. Instead of the traditional programming method by using the external language, a new modeling method was introduced with the help of Digimat. The results indicated that the interface force between (within) EP matrix and nanoparticles, the shell thickness and nanoparticle content play important roles in the reinforcement and fracture of EPNCs. The bending strength increases with the raising of particle content, but decreases with the increasing of shell thickness. The simulated results were consistent with the experiments. The interface force evolves according to the order of interfaces within particles and their shell > matrix-shell > matrix interior. A proper interfacial force can make interfacial debonding and matrix failure occur at the same time, thus improving both the strength and toughness of nanocomposites. This model construction will provide theoretical guidance for nanocomposites design and the clarification of reinforcement mechanism. Graphical abstract: Image 1 Highlights: Cross-examination of analytical, numerical and experimental results is conducted. Appropriate interface, thin shell and particle content play important roles in composites reinforcement mechanism. Finite element evaluation of core-shell nanoparticles reinforced epoxy resin composites wais established.